Marble bust, Sheth Hargovandas Jeevandas - Ghosh, Ayan (2023)
Marble bust of Sheth Hargovandas Jeevandas, who sponsored the bandstand at Jijamata Udyan. He belonged to the Kapol Bania community and was born at Talaja, Bhavnagar, in 1874. In 1932, he started the Mahalaxmi Mills at Bhavnagar. As a businessman, Sheth Hargovandas took a leading part in public affairs and was a trustee in several charitable institutions in Mumbai.